Pengaruh Kepemimpinan Dan Kompetensi Terhadap Produktivitas Pegawai PPSU (Studi Kasus Di Penanganan Prasarana Dan Sarana Umum Pada Kelurahan Lebak Bulus Jakarta Selatan) - Hermawati, Rahmi; Hidayat, Rizky Radhika (Jurnal Ilmiah Sumber Daya Manusia, 2019)
ABSTRACT As for the purpose of this study is to find and obtains evidence empirical and conclusions about influence style leadership and competence of the productivity employees infrastructure and facilities common (PPSU) in urban lebak bulus of south jakarta.            Research methodology used is associative with the quantitative approach. A method of the withdrawal of in the sample have used of these tests are the sampling method of saturated pt pgn promised to supply dating techniques in the entire household sample if all members of a percent of the population used as included in the research sample. Data collection method that we use is to a method of kuosioner and observation to the employees PPSU to officials in urban village lebak bulus of south jakarta . The method of analysis processing the data used was test validity, reabilitas test, test the assumption classical, regression analysis multiple, analysis koefisiensi determination ( r2 ), the hypothesis ( test f and t).            Based on the results of the analysis that has been done obtained that is the or relation a positive and welfare between style leadership and competence to productivity employees together or simultaneous is as much as r = 0,377, this showed that productivity employees at PPSU urban village lebak bulus south jakarta effected by force leadership and competence to a category strong contributing 37.7%, while or 62.3% influenced by other factors out variables tested in pengelitian this.The results of the regression equation is linear multiple namely y = 27,117 + 0,008X1 + 0,817X2 means if the force of leadership (X1) up 1 a unit of then will increase 0,008 and competence (X2) up 1 a unit of then will increase 0,817.Influence between leadership and competence to productivity employees is significant.This can be seen of the value of f count 25,972 > f table 3,10  Key Words : Leadership, Competence , Productivity